Detection of Coliform and Escherichia coli on Ice Cubes from Beverage Sellers around Campus 4 of Universitas Ahmad Dahlan - Aji, Oktira Roka; Fiani, Nofa Nur (Metamorfosa: Journal of Biological Sciences, 2021)
Ice cubes are a complement to drinks. Ice cubes must not contain Coliform or Escherichia coli . Coliform and Escherichia coli are indicator microorganisms used in water quality analysis. Its presence indicates fecal contamination. The purpose of this study was to analyze the presence of Coliform and E.coli on ice cubes found in drinks sold around the Kampus 4 Universitas Ahmad Dahlan. Sampling was done by purposive sampling. The sample used in this study was 7 ice cube samples taken from different stalls around the campus. This study used the MPN (Most Probable Number) method which consists of a presumptive test, a confirmative test and the Escherichia coli test. A positive result was indicated by changes in the turbidity of the media and the presence of gas bubbles in the durham tube. Data analysis was performed by comparing the number of positive tubes in the observation results with the MPN table. Based on the data obtained, samples of ice cubes from 7 sellers around Kampus 4 Universitas Ahmad Dahlan were positive for Coliform and Escherichia coli bacteria. The principles of food sanitation hygiene need to be improved to prevent bacterial contamination on ice cubes.